KONTROL DIRI DAN IMPULSIVE BUYING PADA REMAJA PENGGEMAR K-POP - Syafebti, Dita; Utama Afriyenti, Lenny; Fitriyana, Rika (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
K-Pop has become one of South Korea's successes in introducing its culture to the whole world, one of which is Indonesia. K-Pop music fans in Indonesia tend to be mostly adolescents and are not spared from purchasing merchandise. From the phenomenon in the field, teenagers often buy merchandise without any consideration. This refers to impulsive buying behavior, therefore adolescents need self-control to avoid impulsive purchases. This study aims to determine the relationship between self-control and impulsive buying in adolescents K-Pop fans. This research is a correlational study with quantitative methods. The results of Pearson's product moment correlation calculations show that there is a weak relationship with the direction of a negative relationship between self-control and impulsive buying in adolescents K-Pop fans, with a value of r = -0.365 and with sig. 0.000 (p < 0.05).So it can be concluded that the higher the self-control, the lower the tendency of impulsive buying among adolescents K-Pop fans, and vice versa.